Preparation of superhydrophobic polyethersulfone/zinc oxide nanocomposites for water treatment - Nombasa, Dumile (Vaal University of Technology, 2022)
Membrane distillation is a water desalination method involving evaporation through a hydrophobic, microporous membrane under a vapour pressure gradient between the porous hydrophobic membrane and separating water vapour from a salty water stream by allowing only water vapour and other volatile molecules to pass through the membrane. Polymer membranes utilized in membrane distillation are reliable, with a low cost and low energy demands, are easy to use, produce ultra-pure water, and achieve complete rejection of ions, cells etc. However, these membranes are prone to fouling, resulting in a short lifespan and high energy demand. This work addresses the membrane fouling of Polyethersulfone (PES) functionalised with Zinc Oxide (ZnO) nanomaterials using Non-solvent Induced Phase Separation (NIPS) ) to form flat sheet PES/ZnO nanocomposite membranes of 102 to 142 μm thickness and 53.33 to 56.44 porosity(%). First, ZnO NPs and ZnO NRs were synthesized using the sol-gel and hydrothermal methods, respectively. The formation of the ZnO nanomaterials was confirmed through characterization techniques such as Ultraviolet-visible spectroscopy (UV-Vis), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction spectroscopy, Scanning electron microscope (SEM), Energy dispersive spectroscopy (EDS) and Transmission electron microscope (TEM). The ZnONPs and ZnONRs were then uniformly dispersed into PES polymer blends to fabricate PES/ZnONP and PES/ZnONR nanocomposite membranes. Secondly, the nanocomposite membranes were modified via grafting with low surface energy molecules 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane (PFTS) and 1H,1H,2H,2H-perfluorodecyltriethoxysilane (PDTS). The functionalisation success of the ZnO nanomaterials embedded in the PES/ZnO nanocomposite membranes and their modification membranes were assessed for improved surface properties and confirmed by FTIR, SEM, EDX and OCA. The highest increase in the water contact angle( WCA) was observed from 57° for the pristine membrane to 116° for PES/ZnONP(1%)/PFDS(5%) and 124° for PES/ZnONR(5%)/PDTS(5%) nanocomposite membranes. This work fabricated a novel near superhydrophobic PES/ZnO nanocomposite membrane with enhanced separation properties for high saline water treatment.
M. Tech. (Department of Biotechnology and Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Superhydrophobic Polyethersulfone; Zinc Oxide; Nanocomposites; Membrane Distillation; Hydrophobic/Hydrohilic surfaces; Water desalination method; Nanocomposite membranes; Saline water treatment; Dissertations, Academic -- South Africa.; Nanostructured materials.; Saline waters -- Purification.; Saline water conversion -- Reverse osmosis process.